Metabolic disorders in menopause - Stachowiak, Grzegorz; Pertyński, Tomasz; Pertyńska-Marczewska, Magdalena (Menopause Review/Przegląd Menopauzalny, 2015)
Metabolic disorders occurring in menopause, including dyslipidemia, disorders of carbohydrate metabolism (impaired glucose tolerance – IGT, type 2 diabetes mellitus – T2DM) or components of metabolic syndrome, constitute risk factors for cardiovascular disease in women. A key role could be played here by hyperinsulinemia, insulin resistance and visceral obesity, all contributing to dyslipidemia, oxidative stress, inflammation, alter coagulation and atherosclerosis observed during the menopausal period. Undiagnosed and untreated, metabolic disorders may adversely affect the length and quality of women’s life. Prevention and treatment preceded by early diagnosis should be the main goal for the physicians involved in menopausal care. This article represents a short review of the current knowledge concerning metabolic disorders (e.g. obesity, polycystic ovary syndrome or thyroid diseases) in menopause, including the role of a tailored menopausal hormone therapy (HT). According to current data, HT is not recommend as a preventive strategy for metabolic disorders in menopause. Nevertheless, as part of a comprehensive strategy to prevent chronic diseases after menopause, menopausal hormone therapy, particularly estrogen therapy may be considered (after balancing benefits/risks and excluding women with absolute contraindications to this therapy). Life-style modifications, with moderate physical activity and healthy diet at the forefront, should be still the first choice recommendation for all patients with menopausal metabolic abnormalities.